PERTUMBUHAN DAN KELULUSHIDUPAN IKAN NILA MERAH (Oreochromis sp) YANG DIPELIHARA PADA SALINITAS BERBEDA DENGAN TEKNOLOGI BIOFLOK - Ady Herianto Simanjuntak; Rusliadi Rusliadi; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstrac This research was conducted on october 3rd - November 2nd, 2017 in the technology Aquaculture Laboratory, fisheries and marine faculty, Riau University. The aim of this research was to determine the effect of different salinity for grwoth and survival rate red Nile tilapia using biofloc technology. The method was using the experimental method and completely randomized Design (CRD) with four treatments and three replications , the treatments were : amount of salinity 11 ppt, 13 ppt, 15 ppt and 17 ppt. The result showed that there was the effect of different salinity for absolute growth of weight, specific growth rate and feed efficiency, neverthless there was not effect for absolute of length and food convertion ratio. The best treatment was 17 ppt salinities, gave the absolute growth of weight 2,13 g, specific growth rate 3,47 g, absolut of length 1,83 cm, feed efficiency 102,53%, good convertion ratio 0.97% and survival rate 78,33%.Water quality parameters consists of temperature was around 27-31'C, pH 7-8, Dissolved oxygen (DO) 4-7 mg/l, ammoniak 0,06-0,1 mg/l and the best holding capacity was in 17 ppt , approximately 6,3 ml Keyword: salinity, tilapia, bioflock technology